A Unique Case Report on Hypersensitivity Vasculitis as an Allergic Reaction to the Herpes Zoster Vaccine. (January 2019) - Puram, Vikram; Lyon, Danielle; Skeik, Nedaa
Hypersensitivity vasculitis (HV) or leukocytoclastic vasculitis is a rare small-vessel vasculitis that may occur as a manifestation of the body's extreme allergic reaction to a drug, infection, or other foreign substance. Characterized by the presence of inflammatory neutrophils in vessel walls, HV results in inflammation and damage to blood vessels, primarily in the skin. Histologically, when neutrophils undergo leukocytoclasia and release nuclear debris into the vasculature, vascular damage manifests as palpable purpura. The incidence of HV is unknown and its relationship and interaction with certain vaccinations is rare and poorly understood. Affected patients with HV generally have a good prognosis; however, fatality may occur if organs such as the central nervous system, heart, lungs, or kidneys are involved. We report a unique case of a 60-year-old man who presented with a serious case of HV after receiving the herpes zoster vaccine. A thorough literature review yielded only one similar case of vascular reaction to the varicella vaccine that was reported in the Annals of Internal Medicine in 1997; however, no other reported cases with regard to the herpes zoster vaccine have been found. Our case presents a rare glimpse into HV that may result from varicella vaccine administration.